2024
DOI: 10.1097/gme.0000000000002310
|View full text |Cite
|
Sign up to set email alerts
|

Weight loss response to semaglutide in postmenopausal women with and without hormone therapy use

Maria D. Hurtado,
Elif Tama,
Sima Fansa
et al.

Abstract: Objective To compare weight loss response and changes in cardiometabolic risk markers in postmenopausal women using semaglutide with and without menopause hormone therapy (HT) use. Methods Retrospective cohort study of postmenopausal women treated with semaglutide for overweight or obesity for ≥3 months. Endpoints: total body weight loss percentage (TBWL%) at 3, 6, 9, and 12 months after semaglutide initiation; and percentage of women achieving ≥5% and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…We applaud the clinical intuition of Hurtado et al to investigate the role of hormone therapy (HT) in menopausal obese and overweight women receiving semaglutide therapy in the original study, ''Weight loss response to semaglutide in postmenopausal women with and without hormone therapy use''. 1 This analysis of 106 patients showed a marked advantage for the 16 users of HTwith up to 50% and 33% more weight percentage weight loss as measured quarterly in the first 12 months. They also cite the findings of Papadikis in the OsteoLaus study who demonstrated decreased visceral adipose tissue, body mass index, and android fat mass on serial dual-energy x-ray absorptiometry imaging in current users of HT, but not past users or never users, in the perimenopausal window.…”
mentioning
confidence: 85%
See 1 more Smart Citation
“…We applaud the clinical intuition of Hurtado et al to investigate the role of hormone therapy (HT) in menopausal obese and overweight women receiving semaglutide therapy in the original study, ''Weight loss response to semaglutide in postmenopausal women with and without hormone therapy use''. 1 This analysis of 106 patients showed a marked advantage for the 16 users of HTwith up to 50% and 33% more weight percentage weight loss as measured quarterly in the first 12 months. They also cite the findings of Papadikis in the OsteoLaus study who demonstrated decreased visceral adipose tissue, body mass index, and android fat mass on serial dual-energy x-ray absorptiometry imaging in current users of HT, but not past users or never users, in the perimenopausal window.…”
mentioning
confidence: 85%
“…We applaud the clinical intuition of Hurtado et al to investigate the role of hormone therapy (HT) in menopausal obese and overweight women receiving semaglutide therapy in the original study, ''Weight loss response to semaglutide in postmenopausal women with and without hormone therapy use'' 1 . This analysis of 106 patients showed a marked advantage for the 16 users of HT with up to 50% and 33% more weight percentage weight loss as measured quarterly in the first 12 months.…”
mentioning
confidence: 99%